Analysis of Academic Supervision and Work Motivation with Teacher Performance at SMA Negeri 1 in Maesaan District, South Minahasa Regency - Sumual, Shelty D M (JR Education, 2025)
Teacher performance plays a crucial role in achieving learning objectives. This study will examine issues related to: (1) low work motivation among some teachers, which impacts the teaching and learning process; (2) low teacher performance; and (3) academic supervision has not been implemented in accordance with applicable supervision regulations. The objective of this study is to determine the relationship between academic supervision and work motivation with teacher performance at STATE HIGH SCHOOL 1 in Maesaan District, South Minahasa Regency. The method used in this study is a descriptive survey with a quantitative approach. The population is all teachers at STATE HIGH SCHOOL 1 in Maesaan District, South Minahasa Regency. The sample size is 47. The design used in this study was a correlation product-moment and multiple. Research Results is the correlation value (R) of 0.905 was found based on the interpretation table, which is in the range of 0.80-1.000. Thus, the strength of the relationship between academic supervision and work motivation on teacher performance is in the very strong category. As seen, the sig value is 0.000 <0.01, thus accepting Ha and rejecting H0 based on the test results, thus the hypothesis is supported. This means that if academic supervision and work motivation simultaneously improve, teacher performance will also improve. This is because, based on the research conducted, academic supervision and work motivation have a very strong relationship with teacher performance.